Examining the relationship between vertical coordination strategies and technical efficiency: Evidence from the Brazilian ethanol industry - Sant'Anna, Ana Claudia; Bergtold, Jason S.; Shanoyan, Aleksan; Granco, Gabriel; Caldas, Marcellus M. (My University, 2018)
The sugarcane industry in Brazil, one of the world's leading producers of ethanol and sugar, is undergoing significant changes driven by geographic expansion and technological innovations. These changes are forcing sugarcane producers and processors, to re-evaluate their vertical coordination and growth strategies. This paper presents an empirical analysis of the relationship between the vertical coordination strategies at the production-processing interface of the Brazilian ethanol supply chain and the technical efficiency of the mills. It utilizes data envelopment analysis and a Tobit censored model in combination with unique data on 204 mills that account for around half of Brazil's sugar and ethanol production. Results indicate that vertical integration and the location of the mill have a statistically significant impact on efficiency. The findings show that the technical efficiency is not the main driver of vertical integration implying that such decisions are primarily motivated by strategic considerations. The mills are likely to forgo gains in technical efficiency in exchange for improving their strategic position through vertical integration. These findings shed light on the underlying motivation for the observed level of vertical integration that accompanies the expansion of the Brazilian sugarcane industry. [EconLit citations: L22, Q12, Q16].